Hubungan Sosial Petani Pemilik Sawit Dengan Pekerja Di Desa Kusau Makmur Kecamatan Tapung Hulu Kabupaten Kampar - Ulita Maro Lubis; Teguh Widodo (Peneliti.net, 2026)
Palm gardens are one of the plantation commodities that has an important role in the Indonesian economy especially in Riau. Social relationships are relationships that are intertwined with the existence of mutually beneficial social interactions. The social relations of the palm garden owner and the worker create the pattern of the social relationships of the patron-client created by the existence of mutually beneficial relationships and mutual interaction with each other. Interdependent social relationships qualify Scoot's patron-client pattern. This type of research is qualitative research that is descriptive. Data analysis is by reducing data, presenting data and drawing conclusions, as well as using source triangulation to obtain and validate the research data obtained. Data collection techniques with observations, interviews and documentation. The results of the research show that the social relationship of the palm farmers is an interdependent patron-client social relationship, and a system of employment of workers based on mutual agreement and mutually beneficial trust.